THERMOELECTRIC MATERIALS AND APPLICATIONS - Fozilova Mohira Soyibjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The Peltier effect is a thermoelectric phenomenon where the flow of electric current through a junction of two different materials results in heat absorption at one junction and heat release at the other. This effect, discovered by Jean Charles Athanase Peltier in 1834, is the reverse of the Seebeck effect and plays a crucial role in thermoelectric cooling and heating applications. The Peltier effect is widely utilized in thermoelectric coolers (TECs), which are employed in various sectors including electronics cooling, portable refrigeration, precise temperature control systems, and space exploration. Despite its promising applications, the efficiency of thermoelectric cooling remains a challenge, as the heat dissipation from the hot side requires effective management. This article discusses the fundamental principles of the Peltier effect, its applications, advantages, and limitations, highlighting its significance in modern cooling and heating technologies.